Implementasi Pembelajaran Model Make A Match: Meningkatkan Aspek Keaktifan dan Hasil Belajar Mata Pelajaran Ekonomi - Indarti, Nunuk; Mastiyah, Iyoh (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The implementation of the Make A Match learning model in Economics subjects aims to improve students' activity and learning outcomes. This model utilizes an interactive and enjoyable learning method by comparing and matching Economics concepts. The results of the study showed that the implementation of the Make A Match model provides an improvement in students' activity and learning outcomes in Economics subjects.This study was conducted to investigate the effect of the implementation of the Make A Match learning model on the activity and learning outcomes of students in Economics subjects. This study was carried out using a quasi-experimental method using a pretest-posttest control group design research design. The population in this study was the 11th grade Economics students at one of the high schools in city X. The sample in this study was the 11th grade Economics 1 class as the experimental class and the 11th grade Economics 2 class as the control class. The results of the study showed that there was an improvement in students' learning activity and outcomes after the Make A Match learning model was applied in Economics subjects.Based on the results of the study, it can be concluded that the implementation of the Make A Match learning model can improve students' activity and learning outcomes in Economics subjects. Therefore, the Make A Match model can be applied as an effective alternative learning model to improve students' activity and learning outcomes in Economics subjects.Keywords: Make A Match Model, Learning Activity, Learning Outcomes, Economics